Propuesta de diseño sismo-resistente de columnas cortas en edificaciones de concreto reforzado. - Tello Endara, Juan Carlos (2010)
The city of Riobamba, according to its seismic zoning map, is located in the zone 4, which is considered as the one having the highest seismic risk, this is the reason why it is very obligatory for civil engineers to design their structures in order to resist side loads produced by earthquakes, in this sense, this research work has the goal of helping the seismic-resistant design with a tool which will let us identify the failure type a column element can suffer when confined by walls